ASPEK PERJANJIAN KERJA WAKTU TERTENTU MENURUT KUHPERDATA DI INDONESIA - Irwan Jaya Zay; Suhendro Suhendro; Yetti Yetti (Fakultas Hukum Universitas Borneo Tarakan, 2021)
AbstractAn agreement is an event where one person without a loan or where two people promise each other to do something. The agreement issues an agreement between two people that is made. agreement in the form of a quote containing promises or promises that are spoken or written. The employment agreement is also contained in Article 1601 a BW, namely